The redshift drift as a new cosmological probe - Dutra, Pedro Henrique Bessa Rodrigues (2024)
With the advent of precision cosmology and the next generation of telescopes and sur veys, observations will allow the standard cosmological model to be tested in old and new regimes with unprecedented accuracy, and the data will demand accurate the oretical models of cosmological phenomena in order to be properly interpreted and processed. Theorists are reassessing old and new probes that allow the current cosmo logical paradigm to be tested to its limits. One promising new probe, the measurement which is one of the main objectives of the ELT ANDES spectrograph, is the cosmic redshift drift. One of the theoretical predictions of cosmological models based on Robertson-Walker metrics is the cosmic redshift drift, which measures the real-time rate of change of the spectra of far away sources, and is a generic consequence of cosmological models where the expansion rate is non-constant. Its observation provides a model independent way to measure the time variation of the Universe’s expansion and as such, an independent test of the late-time acceleration phase of the Universe and the existence of a cosmo logical constant. In this thesis we study the redshift drift in realistic cosmological models containing inhomogeneities in the !CDM paradigm. We derive for the first time a gauge-invariant expression for the redshift drift and its power spectrum, and implement the redshift drift f luctuation power spectrum numerically through Einstein-Boltzmann codes and using n-body simulations, providing a solid theoretical foundation for future measurements and observations of the redshift drift in !CDM cosmology and beyond.